Building occupant perception towards waste disposal in residential building / Che Syafawani Che Rahim - Che Rahim, Che Syafawani (Faculty of Architecture , Planning and Surveying, 2015)
This final project academic is about a study of building occupant perception towards waste disposal in residential apartment building. The object for this project are to understand the occupant perception towards waste disposal system that are usually used in residential apartment building, to identify factors that may influence human perception, especially in creating awareness on the issue of waste disposal in residential apartment buildings and to recommend measures that can be taken to increase the participation rate of building occupants and upgrade knowledge in disposing of waste, especially in the area of residential apartment buildings. In achieve the objective, so three residential building chosen as a case study which First Phase Apartment Section 17 Shah Alam, Perdana Apartment Section 13 Shah Alam and Kristal View Condominium Section 7 Shah Alam. Building occupant will be the key to succeed this study where the questionnaires will be distributed to them and most of information will be asked from them. It is important to facilitate the assessment of the current situation occupant perception toward waste disposal in their area. It also main resources to evaluate perspectives and attitudes, especially in urban communities as to create awareness among individual responsibility in solving the problem of waste disposal of residential apartment buildings in the city area.